2015
DOI: 10.3892/etm.2015.2315
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Gram staining for the diagnosis of infections following total hip or knee arthroplasty

Abstract: Abstract. The diagnosis of prosthetic joint infection (PJI)following total joint arthroplasty is difficult for clinicians to make decisions due to the similar symptoms presented by aseptic loosening and infection. Gram staining (GS) is a widely used test but its value remains controversial due to conflicting results in the diagnosis of PJI. The aim of the present study was therefore to evaluate the value of GS in the diagnosis of PJI. Searches using MEDLINE, EMBASE and OVID databases were conducted for data pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…To elaborate, studies have shown that Gram staining of synovial fluid has a poor sensitivity in diagnosing PJI, but its value is mostly evaluated in chronic cases, and may be more useful and sensitive in acute infections. 18 Unfortunately, early molecular detection does not show any benefit so far in acute PJIs, but its diagnostic accuracy maybe optimized in upcoming years. 19 For late acute PJIs caused by another microorganism than S. aureus , the CRIME80 score could be useful in identifying high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…To elaborate, studies have shown that Gram staining of synovial fluid has a poor sensitivity in diagnosing PJI, but its value is mostly evaluated in chronic cases, and may be more useful and sensitive in acute infections. 18 Unfortunately, early molecular detection does not show any benefit so far in acute PJIs, but its diagnostic accuracy maybe optimized in upcoming years. 19 For late acute PJIs caused by another microorganism than S. aureus , the CRIME80 score could be useful in identifying high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, several meta-analyses have been performed to assess the diagnostic accuracy of various established tests for PJI detection (Table 3 and Fig. 5 ) 9 , 10 , 32 43 . Traditionally, periprosthetic tissue culture, which has a positive detection rate of 0.70–0.90, is regarded as the gold standard test for PJI diagnosis 8 , 44 46 .…”
Section: Discussionmentioning
confidence: 99%
“… 42 0.80 (0.74–0.84) 0.95 (0.90–0.98) 17.20 (7.60–38.70) 0.21 (0.17–0.27) 81.00 (35.00–186.00) 0.89 (0.86–0.91) Gram staining Ouyang et al . 43 0.19 (0.12–0.27) 1.00 (0.99–1.00) 41.60 (15.50–111.20) 0.82 (0.75–0.89) 51.00 (18.00–140.00) 0.89 (0.86–0.91) If one diagnostic method was reported by more than one meta-analyses, the most detailed and/or recent one was included in Table 3 . ESR: Erythrocyte sedimentation rate; FDG-PET: 18F-fluoro-2-deoxyglucose positron emission tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Although Gram-staining can be easily used in identifying Gram-positive and Gram-negative bacteria, their results require examination via optical microscopy. Furthermore, false-positive Gram-staining results may be obtained because of high decolorization, excessive heat during fixation, insufficient crystal violet concentration, and Gram-staining-resistant bacteria [ 23 , 24 , 25 ]. Moreover, it is usually recommended that bacteria should be freshly harvested from overnight or extended 18–48 h cultures before Gram-staining [ 26 ].…”
Section: Introductionmentioning
confidence: 99%